The transformative value of professional development. Research into consultants' perspectives regarding training and consultancy - Daniela Frison; Concetta Tino (Firenze University Press, 2019)
This study is based on an analysis of a professional development programme proposed by a training centre in the North of Italy. Twenty-four trainers and/or consultants were involved in a 24-hour training programme in an outdoor setting based on methods and techniques inspired by Experiential Learning. This research connects the literature on and practice of Organizational Development in the field of training and consultancy with the Transformative Learning theory. Within this framework, 14 participants were interviewed to collect qualitative data on their training/consultancy perspectives in order to develop and administer a Training Perspectives Questionnaire to a wider sample, according to a mixed methods approach. This paper presents the results of the first qualitative part.   Il valore trasformativo dello sviluppo professionale. Una ricerca sulle training perspective di consulenti e formatori La ricerca si è sviluppata nell'ambito di un programma di sviluppo professionale proposto da un organismo di formazione del Nord Italia. 24 tra formatori e/o consulenti hanno preso parte ad un percorso di 24 ore basato su metodi ispirati all'Experiential Learning in un contesto outdoor. Il contributo connette la letteratura e le pratiche nell'ambito dell'Organizational Development con la teoria del Transformative Learning. Entro questo framework, 14 partecipanti sono stati intervistati con l'obiettivo di raccogliere dati qualitativi sui valori, gli obiettivi, e le azioni dei formatori e dei consulenti per indagare le loro training perspective. La ricerca seconda un approccio mixed methods, si compone di una prima parte qualitativa, qui presentata, e di una seconda parte quantitativa volta alla costruzione e somministrazione di un Training Perspectives Questionnaire indirizzato a formatori e consulenti.